A reduç\~ao da desigualdade e seus desafios - Claudio Salvadori Dedecca (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This essay explores the reduction of socioeconomic inequality observed during the economic growth in Brazil after 2004. Their results show a significant reduction of economic inequality in terms of current income of the families, explained by the creation of jobs, the income public policy and the public spending. From the point of view of the evolution of social inequality, the essay points to a slow reduction in terms of access to public goods. The results are convergent with a growth pattern backed in consumption, but with limited and unstable investment intensity. The essay concludes, therefore, that the most significant advances in reducing social inequality depend on the ability of the country to establish sustained and distributive dynamics of investment.
Keywords: I30; O15; 330; socioeconomic inequality; growth pattern; public policy; socioeconomic development; poverty